2020
DOI: 10.1029/2020gl087776
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning‐Based Global Atmospheric Forecast Model

Abstract: The paper investigates the applicability of machine learning (ML) to weather prediction by building a reservoir computing-based, low-resolution, global prediction model. The model is designed to take advantage of the massively parallel architecture of a modern supercomputer. The forecast performance of the model is assessed by comparing it to that of daily climatology, persistence, and a numerical (physics-based) model of identical prognostic state variables and resolution. Hourly resolution 20-day forecasts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 17 publications
(24 reference statements)
0
77
0
Order By: Relevance
“…A recent study has shown an increase of MJO prediction skill by correcting model biases with a linear statistical model 34 . Deep learning (DL) techniques have been proven to be a powerful tool for identifying weather and climate patterns 35 37 , sub-grid scale parameterizations 38 , 39 , weather and climate predictions 40 44 , and post-processing of numerical weather forecasts (shorter than 7 days 43 , 44 ). However, post-processing with DL methods has not yet been applied to MJO forecasts.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has shown an increase of MJO prediction skill by correcting model biases with a linear statistical model 34 . Deep learning (DL) techniques have been proven to be a powerful tool for identifying weather and climate patterns 35 37 , sub-grid scale parameterizations 38 , 39 , weather and climate predictions 40 44 , and post-processing of numerical weather forecasts (shorter than 7 days 43 , 44 ). However, post-processing with DL methods has not yet been applied to MJO forecasts.…”
Section: Introductionmentioning
confidence: 99%
“…The ML techniques developed in these references are evaluated on chaotic low-order models such as the Lorenz-96 model (L96, [42]) or the two-scale Lorenz model (L05III, [41]). Moreover, the NN and reservoir models in [22,55,56,3] were tested on genuine meteorological fields.…”
Section: 1mentioning
confidence: 99%
“…There are by mid 2021, dozens of ML papers in the literature dealing with the problem of estimating the dynamics of a system from observation, even when only focusing on typical low-order models used in the field of geoscience. The problem can be addressed by typical ML techniques, such as the projection on a regressor frame or basis, random forests, analogs, diffusion maps, echo state networks, LSTM and other neural network approaches (Brunton et al, 2016;Lguensat et al, 2017;Harlim, 2018;Pathak et al, 2018;Dueben and Bauer, 2018;Fablet et al, 2018;Scher and Messori, 2019;Weyn et al, 2019;Arcomano et al, 2020). It can also be solved using a conjunction of ML and data assimilation (DA) techniques to exploit noisy and incomplete observations such as those met in realistic geoscience systems Brajard et al, 2020;Bocquet et al, 2020a;Arcucci et al, 2021).…”
Section: Parameter Estimation and Data-driven Techniques For The Geosciencesmentioning
confidence: 99%